A Thermodynamic Model for Interpreting Tryptophan Excitation-Energy-Dependent Fluorescence Spectra Provides Insight Into Protein Conformational Sampling and Stability - Kwok, A; Camacho, IS; Winter, S; Knight, M; Meade, RM; Van der Kamp, MW; Turner, A; O’Hara, J; Mason, JM; Jones, AR; Arcus, VL; Pudney, CR (Frontiers in Molecular Biosciences, 2021)
It is now over thirty years since Demchenko and Ladokhin first posited the potential of the tryptophan red edge excitation shift (REES) effect to capture information on protein molecular dynamics. Whilst there have been many key efforts in the intervening years, a biophysical thermodynamic model to quantify the relationship between the REES effect and protein flexibility has been lacking. Without such a model the full potential of the REES effect cannot be realized. Here, we present a thermodynamic model of the protein REES effect that captures information on protein conformational flexibility, even with proteins containing multiple tryptophan residues. Our study incorporates exemplars at every scale, from tryptophan in solution, single tryptophan peptides to multi-tryptophan proteins, with examples including a structurally disordered peptide, de novo designed enzyme, human regulatory protein, therapeutic monoclonal antibody in active commercial development, and a mesophilic and hyperthermophilic enzyme. Combined, our model and data suggest a route forward for the experimental measurement of the protein REES effect and point to the potential for integrating bimolecular simulation with experimental data to yield novel insights.